A Review on Size‐Dependent Mechanical Properties of Nanowires. Issue 8 (21st June 2019) - Nasr Esfahani, Mohammad; Alaca, Burhanettin Erdem
Abstract : The primary challenge to exploit the nanowire as a truly one‐dimensional building block in nanoscale devices is the clear incorporation of scale effects into the operational performance. Size‐dependent behavior in physical properties of nanowires is the subject of intense experimental and computational studies for more than two decades. In this review, the measurement techniques and computational approaches to study scale effects on mechanical properties of nanowires are reviewed for fcc metallic, silicon, and zinc oxide structures. Advantages and disadvantages of each measurement tool are summarized with data reported in the literature. A similar comparison is carried out for computational techniques. Contradictions in the literature are highlighted with an assessment of research needs and opportunities, among which the plastic behavior of gold nanowires and elastic properties of silicon nanowires can be primarily mentioned. Furthermore, challenges associated with the coupling of measurement methods and modeling approaches are summarized. Finally, points of agreement between experimental measurements and computational studies are discussed paving the way for the utilization of nanowires in future nanoscale devices. Abstract : This article reviews achievements made in the determination of the size‐dependent mechanical properties of nanowires. Covering both measurement techniques and computational approaches, data reported in the literature are summarized for a variety of nanowires. With the description of the landscape for the future utilization of nanowires in engineering applications, contradictions, and convergence points are highlighted for research needs and opportunities.